Kinematic interpretation of shearband boudins : new parameters and ratios useful in HT simple shear zones - Pamplona, J. (2011)
Shearband boudins (asymmetric boudins showing slip along the inter-boudin surface, which is synthetic with respect to the bulk shear sense) are ubiquitous and well-exposed in HT simple shear zones. The present work aims to extend the methodology of analysis of shearband boudins developed by Goscombe and Passchier (2003). Such shearband boudins represent complex objects that require an adequate methodology for unambiguous kinematic interpretation. We propose new geometric parameters (Bbs, B-t, c’, D’, d, ψ’) in order to describe and identify, with confidence, the kinematics of boudinage in this particular geological framework. The key-observation for kinematic interpretation in simple shear regimes is the boudin axis (Lb) that is commonly present, excluding the necessity to identify the regional stretching lineation (Lx) in the metasedimentary matrix. In monoclinic HT simple shear zones, this approach involves the use of a local displacement plane (Sx), which is always normal to the boudin axis (Lb).